Planowanie i zasady finansowania inwestycji publicznych na poziomie lokalnym w Polsce w latach 2008–2013 - Opałka, Benedykt (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The aim of the research was to establish the most important economic and administrative factors that had shaped the possibility of using available sources of financing of public investment projects. The analysis was concentrated on attempts to identify and asses the process of regulating general value of public investment at the municipal level. Significant difficulties in maintaining a stable level of financing for the development tasks were rooted mainly in changes in economic conditions, particularly the financial crisis, and from changes in the aces and scope of the EU funds during the programming period 2007–2013.